Gingival Pigmentation and Its Association with Skin Complexion and Periodontal Status Among Patients Attending a Tertiary Hospital in Nigeria: A Cross-Sectional Study (Nigerian Dental Journal, 2026)
Introduction: Gingival color varies among different races and can be affected by a number of factors including pigmentation. Gingival pigmentation is of aesthetic concern in some individuals and has been linked to skin complexion. However, there is paucity in the literature regarding the association between gingival pigmentation and periodontal disease.Methods: This was a cross-sectional study conducted among participants who attended the Periodontology Clinic, University of Port Harcourt Teaching Hospital (UPTH). A convenient, non-probability sampling technique was used to recruit participants who gave consent. Data collection was done using a semi-structured questionnaire, which had three sections. Section A included information on sociodemographics, Section B included intraoral examination to assess periodontal health status, and Section C included assessment of gingival pigmentation and skin pigmentation. The modified Community Periodontal Index (CPI) was used to assess periodontal health status. Gingival pigmentation was assessed using the Dummett-Gupta Oral Pigmentation Index (DOPI) and the index by Ponnaiyan et al., while the Fitzpatrick scale was used to assess skin complexion.Results: There were 114 participants, with age range 17–84 years, M:F = 1:1.38. The prevalence of gingival pigmentation among the participants was 80.7%, with more females presenting with gingival pigmentation than males. More participants from other ethnic groups had heavy pigmentation compared to those from the three common ethnic groups; this finding was not statistically significant (p = 0.746). Skin pigmentation was significantly associated with gingival pigmentation (p < 0.001). There was a statistically significant association between gingival pigmentation and periodontal disease, as more participants with heavy pigmentation had healthy periodontium (CPI 0) compared with participants with pink tissue (p = 0.003).Conclusion: The prevalence of gingival pigmentation in this study was 80.7%. It was higher among participants from the other ethnic groups. Gingival pigmentation was significantly associated with skin complexion and periodontal disease.KEYWORDS: Gingival pigmentation, skin complexion, periodontal status
Keywords: Gingival pigmentation.; Skin complexion; Periodontal status